The role of short linear motifs (SLiMs) in SARS-CoV-2 entry into human cells - Gibson, Toby (Henry Stewart Talks, 2021)
Rationale and approach to investigating ACE2 and integrin SLiMs, Update on the mechanism of ACE2- and integrin-mediated viral entry into cells, SLiMs and their essential role in cellular endocytosis, Possibility of targeting specific SLiMs as a novel antiviral therapy, Efficacy of Chloroquine and Chlorpromazine as potential small-molecule therapeutics against viral entry into cells, The power of interfering with integrin-dependent cellular endocytosis as a proactive defense against coronaviruses